DEMONTRATION LEARNING MODEL APLICATION ON ASSISTED GUIDED INQUIRY BASED PICTORIAL RIDDLES AS EFFORTS TO INCREASE STUDENT MOTIVATION AND STUDENT LEARNING RESULT OF TIK FOR TEN ONE CLASS STUDENT AT KARYA WISATA SENIOR HIGH SCHOOL SINGARAJA AT SECOND SEMESTER ON SCHOOL YEAR 2011/2012 - Ardhana, Komang Rafi (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This research aimed to increase 1)student motivation 2)student learning result in learning TIK with subject using word processing aplication 3)describing student response demontration learning model aplication on assisted guided inquiry based pictorial riddles. This research were class action research involving 35 student from X1 class in Karya Wisata Singaraja senior high school at second semester on school year 2011/2012. the Object of this research are: 1) students’ motivation, 2) students’ learning result , 3) students’ response, 4) the demontration learning model aplication on assisted guided inquiry based pictorial riddles. Students’ motivation data were collected by questionnaire, student learning result were data collected by using poll. The result of research showed that mean score of student motivation before the action 78,03 with low category. After the first cycle action, mean score increased to 95.83 with medium category, and after the second cycle action, score increased to a high category. The average score of learning result in the first cycle with classical completeness 74.9 80% were classified as unresolved. The average score learning cycle II increased to 77.9 with classical completeness 91.1% were classified as complete. Average score of the students responses are 56.6 were classified as positive category. Thus, demontration learning model aplication on assisted guided inquiry based pictorial riddles can increase student motivation and learning result in ten one class at Karya Wisata Singaraja Senior High School on school year 2011/2012.